Promosi Wisata Tambuh Raya Idaman di Desa Condro Kecamatan Pasirian Melalui Pengenalan Permainan Tradisional - Wahyu Dwi Utomo; Nur Akhidatul J; Sigit Prastowo (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Tourism is a crucial economic sector for a region, so it needs attention and development. One of the tourism sectors in East Java is Wisata Tambuh Raya Idaman which is located in Condro Village, Pasirian District, Lumajang Regency, East Java. This tourism is one of the potentials in Condro Village, but public awareness of this tourism is still lacking, so that the community's interest in visiting is also small. In addition, young children prefer to play with their mobile phones rather than playing traditional games or socializing with their friends. Therefore, group 174 of the KKN UMD UNEJ has a work program called PISAO (Tourism Promotion and Preservation of Traditional Games). The methods of this work programs are observation, discussion, practice and evaluation. The results of the KKN UMD UNEJ work program group 174 namely Wisata Tambuh Raya Idaman is better known by the community, increasing the income of residents who open stalls at tourist attractions, storing traditional games, increasing children's interest in playing traditional games and reducing the intensity of playing mobile phones.